HUBUNGAN GAYA KOMUNIKASI KEPEMIMPINAN CAMAT TERHADA KINERJA APARATUR SIPIL NEGARA DIKANTOR KECAMATAN LANGGAM KABUPATEN PELALAWAN - Maharani Dwi Putri; MUhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The role of leadership is very important because a leader is a key figure who is always expected to be able to carry out leadership well and is expected to have the conditions of a leader. A leader must be able to supervise, provide motivation, be able to build good relationships with followers, and can carry out decision-making in a democratic way. If the leader in a government agency does its job well, it will affect the performance and its employees, then the relationship between the leader and management are two interrelated things. Leaders in an institution will have their own characteristics and characteristics according to their respective personalities which reflects how the communication style of leadership and a government institution will be different. The purpose of this study was to determine the relationship of the leadership style of the district leadership communication to the performance of ASN in the Langgam sub-district office in Pelalawan Regency in 2019. The expected benefits of this study provide information to leaders about the communication style that should be applied so as to enhance good cooperationThis research uses an explanative quantitative method, with data collection techniques through distributing questionnaires directly to ASN Performance in the Sub-district Office of Langgam. The sample in this study amounted to 38 respondents with sampling techniques saturated and using Pearson product moment (r) coefficient correlation analysis techniques.Based on the results of research that has been carried out, in the Langgam sub-district office there is a relationship between the leadership style of the camat leadership and the ASN performance in the Pelalawan Sub-district Camat Office with a tcount (9,125)> ttable (2,028) and the resulting significance value of 0,000 is still below 0.05 , then the hypothesis in this study was accepted. From the product moment correlation test results in which the resulting correlation value of 0.836 in the category is very strong, these results explain that the leadership style of communication has a very strong relationship to the performance of ASN in the Sub-District Office of Pelalawan.